Carotid siphon geometry and variants of the circle of Willis in the origin of carotid aneurysms - Silva Neto, Ângelo Raimundo (2012)
This study evaluated anatomical variants in the carotid siphon and of the circle of Willis in patients with aneurysms. We performed a retrospective analysis of cerebral angiographies. The Control Group was composed of patients without aneurysms. Posterior communicating artery (PcomA) aneurysms were more common in women (p<0.05), and the anterior communicating artery (AcomA) aneurysms in men (p<0.1). The incidence of fetal-type PcomA was higher in cases with co-occurring PcomA aneurysm (24 versus 8%, p<0.05). Patients with AcomA aneurysm had higher incidence of A1 hypoplasia (p<0.0001, OR=32.13, 95%CI 12.95–79.71) and lower frequency of fetal-type PcomA compared to their control counterparts (p=0.0125). The angle of carotid siphon was narrower in patients with PcomA aneurysm (27.3±19.1 versus 34.8±22.6, p=0.028). In conclusion, a narrower carotid siphon or the presence of fetal-type PcomA or A1 hypoplasia may cause hemodynamic stress, thereby promoting the formation of aneurysms in susceptible individuals